PLCβ1-SHP-2 complex, PLCβ1 tyrosine dephosphorylation and SHP-2 phosphatase activity: a new part of Angiotensin II signaling? - Rossi Gian (Journal of Biomedical Science, 2011)
Abstract Background Angiotensin II (Ang II) signaling occurs via two major receptors which activate non-receptor tyrosin kinases that then interact with protein tyrosin-phosphatases (PTPs) to regulate cell function. SHP-2 is one such important PTP that also functions as an adaptor to promote downstream signaling pathway. Its role in Ang II signaling remains to be clarified. Results Using cultured normal human fibroblasts, immunoprecipitation and western blots, we show for the first time that SHP-2 and PLCβ1 are present as a preformed complex. Complex PLCβ1 is tyr-phosphorylated basally and Ang II increased SHP-2-PLCβ1 complexes and caused complex associated PLCβ1 tyr-phosphorylation to decline while complex associated SHP-2's tyr-phosphorylation increased and did so via the Ang II type 1 receptors as shown by Ang II type 1 receptor blocker losartan's effects. Moreover, Ang II induced both increased complex phosphatase activity and decreased complex associated PLCβ1 tyr-phosphorylation, the latter response required regulator of G protein signaling (RGS)-2. Conclusions Ang II signals are shown for the first time to involve a preformed SHP-2-PLCβ1 complex. Changes in the complex's PLCβ1 tyr-phosphorylation and SHP-2's tyr-phosphorylation as well as SHP-2-PLCβ1 complex formation are the result of Ang II type 1 receptor activation with changes in complex associated PLCβ1 tyr-phosphorylation requiring RGS-2. These findings might significantly expand the number and complexity of Ang II signaling pathways. Further studies are needed to delineate the role/s of this complex in the Ang II signaling system.